Agro-industrial residues for microbial bioproducts: A key booster for bioeconomy. (December 2022) - Cuadrado-Osorio, Paula Daniela; Ramírez-Mejía, Julieta M; Mejía-Avellaneda, Luis Fernando; Mesa, Leyanis; Bautista, Eddy J
Abstract: Agro-industrial residues are an important source of useful compounds. Colombia produces about 71 billion tonnes of agro-industrial residues per year as a result of the presence of different ecological niches that allow the cultivation of around 200 crops throughout the year. These residues are disposed of mainly in rivers and open fields. This review presents opportunities for a sustainable transformation of the Colombian agricultural and livestock sector by increasing the production of bioproducts with the integration of agro-industrial residues, and the co-production of microbial biomass and metabolites or enzymes in such bioprocesses. Likewise, a framework for the development of bioproduct processes is presented, each stage of which will be studied from a perspective of integration of agro-industrial residues. The use of these underutilized resources has the potential to drive bioeconomic policies and support a circular bioeconomy with a small biotechnology industry in focus. Graphical abstract: Unlabelled Image Highlights: Opportunities for valorization of Colombian agro-industrial residues Bioproduct production process may integrate agro-industrial residues at some stages. Around 71 billion tonnes per year of agricultural residues are produced in Colombia. Strengthening of the bioeconomy sector in the framework of bioproducts development